Composing the Chinese’s Ancient Poetry Songbook Found in Music Textbook for Student at Star Studio in Jinan City, Shandong Province, China - Chen, Wang; Nayos Sartjinpong; Rodchangphuen, Pakorn (วารสารศิลปะและวัฒนธรรมลุ่มแม่น้ำมูล, 2025)
This study used a mixed - method approach with the following objectives. (1) To study the Chinese’s ancient poetry, (2) to compose the Chinese’s Ancient Poetry Songbook, (3) to experiment with teaching by using the songbook, and (4) to evaluate student learning outcomes. Qualitative data were collected through interviews, music composition, and analysis of Chinese’s ancient poetry, while quantitative data were gathered through teaching experiments to assess the effectiveness of the songbook. The findings showed that Chinese’s ancient poetry is an important part of traditional culture, included in the national education policy. The researcher selected 12 poems from the fifth - grade textbook, using Western music theory to create songs and compile a songbook. The songbook has three chapters: an introduction to Chinese’s ancient poetry, basic singing techniques, and the 12 Chinese’s ancient poetry. A 16 - week teaching plan was implemented with 10 students from Star Studio School in Jinan, Shandong, using pre-test and post-tests to measure learning outcomes. Results showed an improvement in student knowledge, with post - test scores increasing from an average of 40.70 to 50.40, and singing performance evaluation scores improving from 40.10 to 50.10 over three tests. The study concluded that the Chinese’s ancient poetry songbook teaching method effectively enhanced students’ learning of Chinese’s ancient poetry and generated interest in the subject.